Propelling a Course-Based Undergraduate Research Experience Using an Open-Access Online Undergraduate Research Journal - Sun, Evelyn; Graves, Marcia L.; Oliver, David C. (Frontiers in Microbiology, 2020)
The University of British Columbia has developed a course-based undergraduate research experience (CURE) that engages students in authentic molecular microbiology research. This capstone course is uniquely built around an open-access online undergraduate research journal entitled Undergraduate Journal of Experimental Microbiology and Immunology (UJEMI). Students work in teams to derive an original research question, formulate a testable hypothesis, draft a research proposal, carry out experiments in the laboratory, and publish their results in UJEMI. The CURE operates in a feedforward manner whereby student-authored UJEMI publications drive research questions in subsequent terms of the course. Progress towards submission of an original manuscript is scaffolded using a series of communication assignments which facilitate formative development. We present a periodic model of our CURE that guides students through a research cycle. We review two ongoing course-based projects to highlight how UJEMI publications prime new research questions in the course. A journal-driven CURE represents a broadly applicable pedagogical tool that immerses students in the process of doing science.